Head Circumference as a Stunting Indicator in Toddlers - Indrawati, Fitri; Nugroho, Kaori Risma Fauzia; Cahyati, Widya Hary (Universitas Negeri Semarang, 2025)
Stunting is a problem of chronic malnutrition marked by disturbance of linear growth in children, resulting from a lack of adequate nutrition, including infection, repetitive infections, and inadequate stimulation. The aim of this study is to analyze the connection between the circumference of the head and stunting incidents in children and toddlers. Research methods used a cross-sectional design with 100 children aged 2-5 years in Central Java. Data was collected through anthropometric measurements ( height, weight, and head circumference) and interviews. Data analysis with univariate and bivariate. Research results show that children with a head circumference not normal to have a prevalence of stunting is higher (21%) compared to children with a normal head circumference (1%), and there is a present connection between head circumference and the incidence of stunting in children ( p-value = 0.016). This study emphasizes the importance of integrating the circumference of the head in monitoring the growth of children, in addition to the conventional anthropometric parameters, for increased effectiveness in preventing stunting. The recommendations study covers a holistic approach involving repair nutrition, health of the mother, and environmental factors.